Efficient hydrogen production from glycerol by steam reforming with carbon supported ruthenium catalysts. (January 2016) - Gallegos-Suárez, E.; Guerrero-Ruiz, A.; Rodríguez-Ramos, I.
Abstract: Various carbon materials differing in surface area, nanostructure and grade of graphitization were used to support ruthenium catalysts for the steam reforming of glycerol. Activity measurements performed in a traditional reactor indicated that the reaction is structure sensitive and the initial activity for hydrogen production of the catalysts decreases with decreasing Ru particle size. Among the most active catalysts, stability in reaction was first related with the graphitization degree of the support. Ru-nanotubes was the most stable with the time on stream, whereas Ru-activated carbon underwent an abrupt deactivation due to carbon gasification. Ru-graphite, the other catalyst with highest initial activity, suffered from a slow deactivation, most likely due to coke formation derived from the olefins produced during reaction. The use of a membrane reactor prevents the formation of these undesired compounds, enhancing the hydrogen yield and rendering a very stable catalyst.